“Levantamiento de procesos operativos en la gestión de la clínica veterinaria sira pets en la ciudad de Sangolquí”. - Llumiquinga Jiménez, Steeven Abraham (2024)
The present entitled work "Lifting of operational processes in the management of the SIRA PETS Veterinary Clinic in Sangolquí city" it is focused on the continuous improvement of the areas into this organization. To achieve the objective, the investigators has been used a qualitative approach that includes direct observations of all the processes carried out in each segment. This approach allows to understand how to carried out in daily practice activities. Due to the notes, has been used divers analytical tools, such as flow charts, process maps and layout, for emphasizing in a clear and structured manner in its ranges. The most relevant element in this methodology is the use of analytical flowcharts, which made to understand the activities carried out in the plan. It allows to identify some alternatives to improvement frequently. The main goal of this study process is the creation of a processes and procedures pamphlet, that has compiles guidelines and recommendations for each area of the organization, it provides a clear and detailed guide about the activities should be carried out in each case. This booklet provides a frame of reference for the clinic's staff, in the continuous improvement the veterinary clinic.